2019
DOI: 10.1186/s12870-018-1627-4
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9-Mediated SlNPR1 mutagenesis reduces tomato plant drought tolerance

Abstract: BackgroundNPR1, nonexpressor of pathogenesis-related gene 1, is a master regulator involved in plant defense response to pathogens, and its regulatory mechanism in the defense pathway has been relatively clear. However, information about the function of NPR1 in plant response to abiotic stress is still limited. Tomato is the fourth most economically crop worldwide and also one of the best-characterized model plants employed in genetic studies. Because of the lack of a stable tomato NPR1 (SlNPR1) mutant, little… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(80 citation statements)
references
References 64 publications
(83 reference statements)
2
78
0
Order By: Relevance
“…Many other studies reported that physical treatment like hyperbaric or low doses of UV irradiation promoted the accumulation of phenolic compounds in tomatoes [35][36][37]; however, in the present study, NSCC coating treatment did not show any additional abiotic stresses on tomatoes. It was also reported that the production of ROS induced lipid peroxidation that resulted in membrane injury and increase the MDA level [38,39]. MDA is an index to test lipid peroxidation and could be considered to represent the level of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Many other studies reported that physical treatment like hyperbaric or low doses of UV irradiation promoted the accumulation of phenolic compounds in tomatoes [35][36][37]; however, in the present study, NSCC coating treatment did not show any additional abiotic stresses on tomatoes. It was also reported that the production of ROS induced lipid peroxidation that resulted in membrane injury and increase the MDA level [38,39]. MDA is an index to test lipid peroxidation and could be considered to represent the level of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, citrus resistance to canker was significantly improved by editing CsLOB1 with the CRISPR/Cas9 system 15 . Targeted editing of SlNPR1 was performed to alter the drought resistance of tomato 16 . Moreover, the heading stage of rice was accelerated, and the yield of oilseed rape was increased by editing Hds 17 and ALC 18 , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the upregulation of LEA genes, the expression of eleven PR genes was upregulated in OsC3H10 OX plants. PR genes are the main components of plant defense mechanisms against biotic stresses, but their functions in abiotic stress have also been reported in plants [ 37 , 38 , 39 ]. Specifically, the overexpression of Arabidopsis PR1 , PR2 and PR5 in Arabidopsis enhances drought tolerance [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the overexpression of two rice OsPR10 family genes conferred drought tolerance in rice plants [ 38 , 40 ]. Moreover, a mutation in NONEXPRESSER OF PR GENES 1 ( NPR1 ), an upstream regulator of the PR gene, reduced drought tolerance in tomato [ 39 ]. Thus, the upregulation of LEA and PR genes by OsC3H10 overexpression could contribute to enhanced drought tolerance.…”
Section: Discussionmentioning
confidence: 99%